A identidade do aluno-adolescente no ambiente escolar e nas redes sociais em uma escola particular de Aracaju-SE - Garcez, Karoline Gandolpho (2020)
Studies about teenagers have been increasing in society nowadays. On that wise, this dissertation aims to understand how identities of adolescent students are set in both school environments and social networks, and which way they differ from or intertwine with each other. It is grounded on studies related to adolescent identity and aligned with the qualitative and interpretive approach. A WhatsApp group with students from a private school of the city of Aracaju, in Brazil, was created with a view to discuss topics related to their daily conversations. In addition, they were also assigned to attend some classes that approached the same topics discussed in the same WhatsApp group. The adolescent identity was analyzed from Bauman’s (2005, 2018) and Gee’s (2004) perspectives, considering the school environment as an offline setting and the social networks as an online setting. Further analyses of the conversations in the WhatsApp group and the attended classes were done according to Gee’s three identity views: the real identity (the everyday type, which can be multiple), the virtual identity (it is portrayed in online settings and may be very different from the real identity) and the projective identity (when the person projects their values and desires onto their online character). Yet, some adaptations of such concepts were necessary in order to better understand the identities of the students. Hence, the virtual identity was taken into consideration when the adolescents would perform it when they could or needed it, yet not always accepted; the real identity was considered as the one they would demonstrate in their everyday lives; and the projected identity could be considered as a blending between their virtual and real identities, at particular moments. In the end of this study, an analysis about the identities of each adolescent student who participated of this research is done, based on the concepts here presented.